PERTANGGUNGJAWABAN PELAKU USAHA ATAS KERUGIAN WISATAWAN MENURUT UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN - Ababil, Maulana Rouf; Sugiarti, Yayuk; Fithry, Abshoril (Jurnal Jendela Hukum, 2023)
According to the Law of the Republic of Indonesia Number 10 of 2009 concerning tourism, it is stated that tourism is a variety of tourist activities and is supported by various facilities and services provided by the community, businessmen, government and local governments. The formulation of the problem of this thesis is how is the form of legal protection for tourists and how is the form of responsibility of tourism business actors towards tourists. The purpose of writing this thesis is to find out and get a solution from the formulation of the problem. The research method in writing this thesis is normative by using a statutory approach with several sources of primary and secondary legal materials, as well as tracing legal materials through legislation and other literature. In the context of legal protection for tourists, what needs to be protected is the rights of tourists. Every tourist has the right to comfort, safety and to get fair treatment and the best possible service from the country where the person concerned visits the tourist spot. Countries where tourists visit must provide security and safety for tourists based on existing laws and regulations. Law Number 10 of 2009 concerning Tourism already regulates the rights and obligations of tourists and tourism entrepreneurs. Article 20 regulates the rights of tourists, including: accurate information about tourist attractions, tourism services in accordance with standards, legal protection and security, health services, protection of personal rights, and insurance protection for high-risk tourism activities.